The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.3748/wjg.v5.i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of polydatin against CCl4-induced injury to primarily cultured rat hepatocytes

Abstract: AIM To investigate the protective effects of polydatin (PD) against injury to primarily cultured rat hepatocytes induced by CCl4. METHODS Rat hepatocytes were separated by methods of liver infusion in vivo and cultured medium (7.5×10 5 cells/mL). Two mL or 0.2mL was added into 24-well or 96-well plates respectively. Twenty-four hours after cell preculture, PD at concentrations of 10 -7 mol/L-10 -4 mol/L was added into each plate. At the same time injury to hepatocytes was induced by adding 10mmol/L-CCl 4 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Polydatin (3,4′,5-trihydroxystibene 3-beta-mono-D-glucoside) (l " Fig. 1 A) has been widely studied because of its vast pharmacological activities, including inhibiting the production of inflammatory mediators [12], inducing production of antioxidants [13], regulating immune function [14], preventing mutations [15], inducing the apoptosis of tumor cells [16], protecting the liver [17] and preventing cardiovascular disease [18]. It has been demonstrated that the biomedical properties of resveratrol (trans-3,5,4′-trihydroxystilbene) are similar to those of polydatin as mentioned above despite their disparate polarities (l " Fig.…”
Section: Emsamentioning
confidence: 99%
“…Polydatin (3,4′,5-trihydroxystibene 3-beta-mono-D-glucoside) (l " Fig. 1 A) has been widely studied because of its vast pharmacological activities, including inhibiting the production of inflammatory mediators [12], inducing production of antioxidants [13], regulating immune function [14], preventing mutations [15], inducing the apoptosis of tumor cells [16], protecting the liver [17] and preventing cardiovascular disease [18]. It has been demonstrated that the biomedical properties of resveratrol (trans-3,5,4′-trihydroxystilbene) are similar to those of polydatin as mentioned above despite their disparate polarities (l " Fig.…”
Section: Emsamentioning
confidence: 99%
“…PD reduces lipid profile in hyperlipidemic rabbits (Xing et al, 2009) and exerts the neuroprotective effect on cerebral injury induced by ischaemia/reperfusion (Cheng et al, 2006). Also, it protects the primarily cultured rat hepatocytes against CCl 4 -induced injury (Huang et al, 1999) and reduces lipid oxidation (Pan et al, 2007). Nonetheless, there has been no report on the reproductive effect of PD on arsenic-induced toxicity in rats, yet.…”
Section: Introductionmentioning
confidence: 97%
“…Polydatin exhibits favorable fall hematic fat action, which decreases the serum levels of total cholesterol (TC), triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C), reduces the content of hepatic TG, and depresses the ratios of LDL-C/high-density lipoprotein cholesterol (HDL-C) and TC/HDL-C in hyperlipidemic hamster [16] and rabbit models [17]. CCl 4 -induced rat hepatocyte injury in vitro can also be evidently alleviated by polydatin via regulation of SOD and MDA levels [18]. Nevertheless, there have been no reports on the protective effects of polydatin against liver injury in vivo, as far as we are aware.…”
Section: Introductionmentioning
confidence: 99%